A Optimization of Direction Finder in Disclosing Cases of Threatening By Jatanras Unit, Criminal Research Unit, Surabaya City Police Office - Andre Marco Julianto; Aris Fernando Matanari; Sardika Yusuf Ramadan Karepesian (Tanggon Kosala, 2024)
This final assignment aims to describe the stages of use in disclosing cheating cases in the jurisdiction of the Surabaya Police and to describe and analyze the factors that can influence the effectiveness/success of using a Direction Finder to reveal cheating cases in the jurisdiction of the Surabaya Police and the optimal performance of investigators at the time. Make disclosures. This sophisticated tool called a Direction Finder, can carry out profiling and track accurately using the perpetrator's cellphone number. This can increase the disclosure of criminal acts, especially cheating. This thesis uses analysis tools, namely the concept of weighted theft, the Direction Finder concept, the optimization concept, and police operational management, as well as SWOT analysis theory and POAC management theory. This final assignment presents qualitative data analysis from the Surabaya Police Criminal Investigation Unit, especially the Jatanras Unit. The findings in the research are that the author found that the only police station with this sophisticated tool is the Surabaya Police Station, and valid data from the Surabaya Police Direction Finder operator support this final project. The conclusion is that using a Direction Finder in disclosing cheating cases is effective despite internal and external factors. Keywords: Direction Finder, Curat, Using, Polrestabes Surabaya